Modeling, evaluation, and optimization for 6G network architecture - WANG Xiaoyun; LU Lu; LIU Chao; SHI Nanxiang; ZHANG Tong; PAN Xiaohan (Tongxin xuebao)
Facing the challenges of increased complexity in 6G network architecture design and deployment due to diverse network scenarios and the pluralization of network elements, a digital twin-based method for modeling, evaluating, and optimizing the 6G network architecture was proposed. Initially, the intricate elements in the network architecture were systematically categorized, leading to the establishment of a three-domain model comprising service, logical, and physical domains in the digital twin space. Subsequently, the three domains and their intricate relationships were modeled in detail using hypergraph theory. Furthermore, the concept of network architectural entropy was introduced to quantitatively assess the rationality of the design and deployment scheme of the 6G network architecture. Finally, a method for constructing 6G network architectural entropy was proposed, and the design idea of 6G network architecture entropy reduction was developed and formulated. Simulation results demonstrate that the proposed architecture entropy reduction theory can quantitatively evaluate the pros and cons of 6G network architecture design and deployment schemes in various scenarios and offer optimal design guidance.